What can we do with 1000 plastid genomes?. (30th March 2017) - Tonti‐Filippini, Julian; Nevill, Paul G.; Dixon, Kingsley; Small, Ian
Summary: The plastid genome of plants is the smallest and most gene‐rich of the three genomes in each cell and the one generally present in the highest copy number. As a result, obtaining plastid DNA sequence is a particularly cost‐effective way of discovering genetic information about a plant. Until recently, the sequence information gathered in this way was generally limited to small portions of the genome amplified by polymerase chain reaction, but recent advances in sequencing technology have stimulated a substantial rate of increase in the sequencing of complete plastid genomes. Within the last year, the number of complete plastid genomes accessible in public sequence repositories has exceeded 1000. This sudden flood of data raises numerous challenges in data analysis and interpretation, but also offers the keys to potential insights across large swathes of plant biology. We examine what has been learnt so far, what more could be learnt if we look at the data in the right way, and what we might gain from the tens of thousands more genome sequences that will surely arrive in the next few years. The most exciting new discoveries are likely to be made at the interdisciplinary interfaces between molecular biology and ecology. Significance Statement: In 2016, the 1000th plastid genome was released by NCBI Genbank. Here we discuss how these sequences have informed studies across plant biology, including systematics, evolutionary biology, molecular biology, photosynthetic physiology, population genetics and ecology.